2020
DOI: 10.34172/jrhs.2020.34
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Aggression and Associated Factors among Iranian Adult Population: A National Survey

Abstract: Background: This survey was conducted to determine the level of aggression among the Iranian adult population and underlying predisposing factors. Study design: A cross-sectional study. Methods: This cross-sectional study included 10,957 participants, involving 23 out of the 31 provinces of Iran in 2019. The outcome of interest was aggression, evaluated by the Buss & Perry aggression questionnaire. The association between aggression and 34 demographic, behavioral, social, and cultural characteristics was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This cross-sectional study presents comprehensive ndings regarding the factors associated with aggression in the general population. The previous study also included the general population, but its focus was on the demographic, behavioral, social, and cultural characteristics [25]. The results of this study highlight the complex interplay between sociodemographic, physical, and psychological factors in uencing aggression levels.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This cross-sectional study presents comprehensive ndings regarding the factors associated with aggression in the general population. The previous study also included the general population, but its focus was on the demographic, behavioral, social, and cultural characteristics [25]. The results of this study highlight the complex interplay between sociodemographic, physical, and psychological factors in uencing aggression levels.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, a study conducted in East Asia reported relatively higher aggression scores than ours. Furthermore, a study conducted in Iran (n = 10,957) reported a mean aggression score of 77.7 (SD = 22.5) [25]. Young adults in Pakistan (n = 500) reported a mean score of 78.0 (18.6) [18].…”
Section: Discussionmentioning
confidence: 99%
“…50 Poorolajal reported that the prevalence of aggression among the Iranian adult general population is higher in singles. 51 Furthermore, single older adults had a higher QoL due to having better communication with their network of friends. 4 ADL was established to be an influential factor in PCS.…”
Section: Discussionmentioning
confidence: 99%